Fungsi Pengawasan Bantuan Operasional Sekolah (BOS) Dinas Pendidikan Kota Manado (Suatu Studi di SDN 04, SDN 21 dan SDN 100 Kota Manado) - Sumual, Natalia; Dengo, Salmin; Londa, Very (Sam Ratulangi University, 2016)
Abstract: The supervisory function is an essential part of the management process Operational Assistance(BOS). The purpose of this research is to find out how the supervisory functions of the Fund Schooloperational assistance (BOS) by Education Office city of Manado. The research method used is descriptivequalitativemethod. The location of the research on select three SDN from SDN 04 Manado, Manado, andSDN 21, SDN 100 Manado. Informant research as many as eight people: Head of education city of Manado(one person), the management team School operational assistance BOS from city Education Office (oneperson), Headmaster (three people) and a school Committee/student parents People (three people) datacollection Techniques used are interviews. Data analysis was done with a descriptive-qualitative analysistechniques, interactive model of the Miles and Hubernann. Based on research results drawn conclusion: Thesupervisory function and Operational Assistance School by the education service Manado well implementedthrough the use of the means/methods of supervision that exists: the implementation of the technicalinstructions consistently BOS by schools, socialization and coaching against the school in the managementand reporting of the Fund's School operational assistance (BOS), monitoring or monitoring on a regularbasis, the implementation of the reporting system by the BOS of the school funds on a regular basis, and theevaluation of the implementation of the Fund's School operational assistance (BOS) at the school. Referringto the conclusions of the study results presented suggestions: (1) to be more effective the supervisory functionsof the Fund's boss, let the Manado City Education Office parties set the school superintendent accompanyingthe management team School operational assistance (BOS) in doing the monitoring and supervision of fundmanagement School operational assistance (BOS) at school. (2) the functional Supervision by supervisoryinternal functional apparatus (inspectorates or supervisory area) need to be implemented to support thesupervisory funded by the management team of the city Education Office School operational assistance (BOS)in supervising and checking the use and the School operational assistance BOS at the school. This isimportant to prevent diversion/use of funds misappropriation by the School operational assistance (BOS) ofthe school.Keywords: Functions Of Surveillance, Fund School operational assistance (BOS)